(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research is based on the problem of low student motivation and learning outcomes in English subjects, which is caused by the use of conventional learning methods that are less attractive. The purpose of this study is to determine the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model assisted by Kahoot in improving student learning outcomes. This study employed a quantitative approach with a quasi-experimental method, using a pretest-posttest control group design. The samples is two classes: class XI-6 as the experimental group and class XI-7 as the control group, each consisting of 25 students. The experimental class was taught using the STAD model with Kahoot, while the control class used conventional learning methods. Data were collected through tests, interviews, and observations, and analyzed using SPSS with normality test, homogeneity test, and hypothesis testing. The results showed a significant improvement in the posttest scores of the experimental class compared to the control class. The hypothesis testing using independent sample t-test yielded a significance value of 0.047 < 0.05, indicating a significant difference in learning outcomes between the two classes. This proves that the use of the STAD cooperative learning model assisted by Kahoot has a positive and significant effect on students’ English learning outcomes.